The effectiveness of topical fluoride agents on preventing development of approximal caries in primary teeth: a randomized clinical trial - Parach Sirivichayakul; Varangkanar Jirarattanasopha; Araya Phonghanyudh; Pitchaya Tunlayadechanont; Ploychompoo Khumsub; Duangporn Duangthip (BMC Oral Health, 2023)
BACKGROUND: This 18-month randomized clinical trial aimed to compare the effectiveness of two topical fluoride applications versus placebo control on preventing development of approximal caries in primary teeth. METHODS: Preschool children were recruited if they had at least one initial approximal carious lesion at the distal surface of the canines, both approximal surfaces of the first molars, or the mesial surface of the second molars assessed from bitewing radiographs. The participants were randomly allocated into 3 intervention groups: Group 1 (placebo control), Group 2 (5% sodium fluoride [NaF] varnish), and Group 3 (38% silver diamine fluoride [SDF]). All agents were applied semiannually. Two calibrated examiners evaluated the caries development from bitewing radiographs. Caries development was recorded when the baseline sound surface or initial approximal carious lesion surface developed dentin caries (beyond the outer one-third of dentine) at the follow-up examination. The intention-to-treat approach was adopted. The Chi-square test was used to analyze the effectiveness of topical fluoride agents in preventing approximal caries development and the effect of other variables. The multi-level logistic regression analysis was performed to assess the relative effectiveness of topical fluoride agents in preventing approximal caries development at the 18-month follow-up. RESULTS: test). After adjusting for confounding factors and clustering effect, the multilevel logistic regression analysis showed no differences in caries development rates between the 3 groups (P > 0.05). Tooth type and the extent of a carious lesion at baseline were the significant factors for caries development. CONCLUSION: At 18-month follow-up, after adjusting for confounding factors and clustering effect, there were no statistically significant differences in preventing of approximal caries development between the semiannual application of 5%NaF, 38%SDF, or placebo. TRIAL REGISTRATION: The study was registered in the Thai Clinical Trials Registry under the number TCTR20190315003 on 15/03/2019.
Keywords: Dental Health and Care Utilization; Fluoride Effects and Removal; Dental materials and restorations